Escherichia coli thymidylate synthase: amino acid substitutions by suppression of amber nonsense mutations. - Michaels, M L (1990)
By using site-directed oligonucleotide mutagenesis, amber nonsense stop codons (5'-TAG-3') have been introduced at 20 sites in the Escherichia coli thymidylate synthase gene. By transforming the thyA mutant plasmids into 13 strains, each of which harbor different amber suppressor tRNAs, we were able to generate over 245 amino acid substitutions in E. coli thymidylate synthase (EC 2.1.1.45). Growth characteristics of these mutants have been studied, yielding a body of information that includes some surprising results in light of the recently published crystal structure of the enzyme.